Plasma antioxidant responses and oxidative stress following a soccer game in elite female players - Andersson, H.; Karlsen, A.; Blomhoff, R.; Raastad, T.; Kadi, F. (Scandinavian Journal of Medicine & Science in Sports, 2010)
We aimed to investigate markers of oxidative stress and levels of endogenous and dietary antioxidants in 16 elite female soccer players in response to a 90-min game (average intensity 82±3% HRpeak). Blood samples were taken before, immediately and 21 h after the game. Plasma-oxidized glutathione, the ratio of reduced to oxidized glutathione (GSH:GSSG) and lipid peroxidation measured by d-ROMs were used as markers of oxidative stress. Plasma endogenous [uric acid, total glutathione (TGSH)] and dietary antioxidants (?-tocopherol, ascorbic acid, total carotenoids and polyphenols) were analyzed using liquid chromatography and the Folin-Ciocalteu method. Exercise induced an acute increase (P<0.05) in GSSG, uric acid, TGSH, ?-tocopherol, and ascorbic acid. In parallel, the GSH:GSSG ratio and polyphenols decreased (P<0.05). GSSG, GSH:GSSG ratio, uric acid, TGSH, and ascorbic acid returned to baseline at 21 h, while polyphenols and ?-tocopherol remained altered. Total carotenoids increased above baseline only at 21 h (P<0.05). Lipid peroxidation, measured by d-ROMs, remained unchanged throughout the study. Thus, intermittent exercise in well-trained female athletes induces a transient increase in GSSG and a decrease in the GSH:GSSG ratio, which is effectively balanced by the recruitment of both endogenous and dietary antioxidants, resulting in the absence of lipid peroxidation measured by d-ROMs.